Experimental study to establish an evaluating method for the responsiveness of liquid flowmeters to transient flow rates. (December 2021) - Furuichi, Noriyuki; Kar-Hooi, Cheong; Yoshida, Taiki
Abstract: An aim of this research work is to establish an evaluation method concerning a responsiveness of flowmeters for a transient flow rate. To this end, reference flow metering systems for the transient flow are proposed in this paper. Because a behavior of the responsiveness depends on the type of flowmeter, evaluations using different parameters, such as response time to sudden rise and sudden fall in flow rate, response to the frequency and amplitude of flow pulsation, mean characteristic and so on are needed. To achieve a precise evaluation, two reference flow metering methods for transient flow rates are proposed in this paper. One is a high-response weighing method and the other is a velocity profile measurement method using the ultrasonic pulsed Doppler method (UPDM). Since the behaviors of the transient flow rate measured by both methods show good agreement, we conclude them to be useable as a reference flow metering system. Highlights: A flow facility for transient flowrate is established to evaluate a responsiveness of flowmeters. The responsiveness for Coriolis, vortex, turbine, ultrasonic, electromagnetic flowmeters are examined. The reference flow metering system for transient flow rate is established using high response weighing tank system. The potential of ultrasonic Doppler method as the reference flow metering is reported.